Endodontic treatment of third molars from a conservative perspective. A case report - Luis Darìo Pèrez Villalba; Fernando Marcelo Armijos Briones (Medisur)
Endodontic treatments of third molars are extremely difficult because they are located posteriorly, have unpredictable internal anatomy, strange occlusal anatomy, and unusual eruption patterns. A 28-years-old patient who attended the doctor’s office for endodontic treatment of the upper right third molar it is presented. Intraoral periapical radiography revealed a slight curvature in the mesial and distal canals. A wide trapezoidal access was prepared after the use of intermediate size files for apical preparation. K-type files No. 6, 8 and 10 were used for the preparation of the smooth tunnel (glide path) and a WaveOne Gold primary file for shaping. A single cone obturation was performed. The case is published with the purpose of offering a clear and complete vision of the endodontic treatment of the mandibular third molar that can have different internal configurations. Third molars, due to their posterior location, limited access, and severe curvature, pose the greatest clinical challenges and require meticulous skill, advanced technology, and patience to succeed.